2019
DOI: 10.1186/s12860-019-0242-z
|View full text |Cite
|
Sign up to set email alerts
|

Aurora A site specific TACC3 phosphorylation regulates astral microtubule assembly by stabilizing γ-tubulin ring complex

Abstract: BackgroundAstral microtubules emanating from the mitotic centrosomes play pivotal roles in defining cell division axis and tissue morphogenesis. Previous studies have demonstrated that human transforming acidic coiled-coil 3 (TACC3), the most conserved TACC family protein, regulates formation of astral microtubules at centrosomes in vertebrate cells by affecting γ-tubulin ring complex (γ-TuRC) assembly. However, the molecular mechanisms underlying such function were not completely understood.ResultsHere, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Additionally, modulating proteins are likewise vital for the regulation of centrosomal microtubule nucleation [ 12 ]. For example, TACC3 (transforming acidic coiled-coil-containing protein 3) has been found to stabilize γ-TuRC assembly from γ-TuSC [ 71 , 72 ]. The building components of γ-TuRC and its regulating proteins (activating, targeting, and anchoring) in the interphase centrosomes are summarized in Table 1 .…”
Section: γ-Tubulin and Microtubule Nucleation By γ-Tubulin Complexesmentioning
confidence: 99%
“…Additionally, modulating proteins are likewise vital for the regulation of centrosomal microtubule nucleation [ 12 ]. For example, TACC3 (transforming acidic coiled-coil-containing protein 3) has been found to stabilize γ-TuRC assembly from γ-TuSC [ 71 , 72 ]. The building components of γ-TuRC and its regulating proteins (activating, targeting, and anchoring) in the interphase centrosomes are summarized in Table 1 .…”
Section: γ-Tubulin and Microtubule Nucleation By γ-Tubulin Complexesmentioning
confidence: 99%
“…However, inhibition of TACC3 expression has been detected as well [15]. It seems therefore that TACC3 plays different roles in different types of cancer [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…It regulates the formation of microtubules throughout the cell cycle [1][2][3]. A great number of studies have shown that TACC3 is highly expressed in gastric cancer, cholangiocarcinoma, multiple myeloma, osteosarcoma, prostate cancer, glioblastoma and non-small cell lung cancer, and breast cancer [3][4][5][6][7][8][9][10][11][12]. However, inhibition of TACC3 expression has been detected in ovarian and thyroid cancers [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins likely affect microtubule nucleation more indirectly. As an example, TACC3 (transforming acidic coiled-coil containing protein 3) stabilizes γ-TuRC during its assembly from γ-TuSC (Singh et al, 2014;Rajeev et al, 2019). On the other hand the putative tumor suppressor cyclin-dependent kinase five regulatory subunitassociated protein 3 (CDK5RAP3; C53) (Wang et al, 2007), which exerts multiple functions in cell cycle regulation, DNA damage response, cell invasion, and ER homeostasis (Sheng et al, 2021), interacts with γ-TuRC and acts as a negative regulator of microtubule nucleation.…”
Section: γ-Turc Recruitment To Centrosomementioning
confidence: 99%